2022
DOI: 10.3390/jcm11247497
|View full text |Cite
|
Sign up to set email alerts
|

Association between Psychological Status and Condylar Bony Changes in Adults: A Retrospective Survey-Based Study

Abstract: Background: This article studies the association between psychological status and condylar bony changes in adults and assesses psychological questionnaires as an indicator of potential condylar bony changes. It is meaningful because condylar bony changes, a severe subtype of TMD and big concern in orthodontic treatment, would likely be ignored in patients with few TMD symptoms, in which case, even with potential psychological problems (depression, somatization and anxiety) being noticed, orthodontists may unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Nevertheless, the question of whether speci c clinical features are linked to an increased risk of developing SBAs remains a matter of debate. Some authors failed to establish a correlation between TMJ pain parameters and CBCT-observed TMJ condylar SBA changes [8, [17][18][19][20][21], while others reported a signi cant association between TMJ pain ndings and those of TMJ condylar SBA alterations [22][23][24][25][26][27][28]. They found a signi cant relationship between TMJ pain and dysfunction parameters and condylar resorption [22], overall destructive changes [23], osteophytes and attening [28], and categorized condylar SBA changes [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the question of whether speci c clinical features are linked to an increased risk of developing SBAs remains a matter of debate. Some authors failed to establish a correlation between TMJ pain parameters and CBCT-observed TMJ condylar SBA changes [8, [17][18][19][20][21], while others reported a signi cant association between TMJ pain ndings and those of TMJ condylar SBA alterations [22][23][24][25][26][27][28]. They found a signi cant relationship between TMJ pain and dysfunction parameters and condylar resorption [22], overall destructive changes [23], osteophytes and attening [28], and categorized condylar SBA changes [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%